PERUBAHAN TRADISI TEPUK TEPUNG TAWAR DALAM PERNIKAHAN ADAT MELAYU DI DESA AIR BALUI KECAMATAN KEMUNING KEBUPATEN INDRAGIRI HILIR - Susi Widiarti; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in Air Balui Village, Kemuning District, Indragiri Hilir Regency. The purpose of this study is to explain the views of traditional leaders regarding the procedures for the practice of the freshwater pat flour ceremony in Malay traditional marriages and explain the shifts in the freshwater tap ceremony practice. The research subjects involved in this study were 1 traditional leader, 1 traditional member, 1 village official and 2 community members in Air Balui Village, Kemuning District, Indragiri Hilir District. This research used a qualitative descriptive approach. The method used is observation, documentation and in-depth interviews. Checking data from various sources is carried out through technical triangulation as an effort to increase the researcher's understanding of what has been found. From the results of the research conducted, it shows that: 1) There has been a shift in the implementation of the plain flour patting tradition at weddings where in ancient times they used drums while currently using modern musical instruments. In addition, the duration of the implementation in the past was 2-4 hours, while now it is shortened to a short time. 2) In the view of traditional leaders, the implementation of plain flour pats in marriage has a good meaning. In addition, people who do not carry out this tradition are also not given any sanctions by the traditional elders. Keywords : Traditional Figures, Views and Shifts